2002
DOI: 10.1177/03635465020300031101
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and Histologic Analysis of the Tibial Tunnel after Allograft Anterior Cruciate Ligament Reconstruction in Goats

Abstract: Tibial tunnel enlargement, consistent with that seen in humans after allograft anterior cruciate ligament reconstruction, did not appear to affect the ultimate incorporation of the allograft on a histologic level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…14 Fink et al and Harris et al reported that enlargement occurs particularly within first 6 weeks after operation and no further increase is observed 2 years after operation. 12,33 We have also noted maximum tunnel enlargement during first 2 months after surgery.…”
Section: Discussionmentioning
confidence: 55%
“…14 Fink et al and Harris et al reported that enlargement occurs particularly within first 6 weeks after operation and no further increase is observed 2 years after operation. 12,33 We have also noted maximum tunnel enlargement during first 2 months after surgery.…”
Section: Discussionmentioning
confidence: 55%
“…The results (Table 1) show that of 141 searches performed in PubMed only 16 yielded results totalling 35 papers. Of these, seven related to the periodontal ligament (Albair et al, 1982;Bragger et al, 1990;Fernyhough and Page, 1983;Isidor et al, 1985;Karring et al, 1985;Luder and Zappa, 1998;Nishimura et al, 1989), and four related to experiments in non-human animals (Harris et al, 2002;Hashimoto et al, 2007;Miyakoshi et al, 2010;Suliman et al, 1997). Of the remaining papers, seven focus on one specific condition: calcific tendinitis (Cahir and Saifuddin, 2005;Chadwick, 1989;Dürr et al, 1997;El-Essawy and Vanhoenacker, 2012;Fritz et al, 1994;Hayes et al, 1987a;Ikegawa, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Input into PubMed took the form: "fibrous enthesis" AND rupture. et al, 1982;Bragger et al, 1990;Fernyhough and Page, 1983;Harris et al, 2002;Hashimoto et al, 2007;Isidor et al, 1985;Luder and Zappa, 1998;Nishimura et al, 1989 Cahir andSaifuddin, 2005;Chadw ick, 1989;Durr et al, 1997;El-Essaw y and Vanhoenacker, 2012;Hayes et al, 1987;Ikegaw a, 1996…”
Section: Discussionmentioning
confidence: 99%
“…However all of these studies use bone containing grafts (BTB tendons) [22,38,46,48]. It is possible that the bone-to-bone healing is a factor in allograft processed tissue, although no data specifically address this issue, and it is possible that there is slower healing theoretically exhibited by exclusively soft tissue grafts [23,37,42]. This may lead to an increased rate of failures secondary to graft stretch with repetitive tensioning, but this concept is yet unproven clinically.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there may be issues regarding graft incorporation and healing [3,4,13,15,17,23,32]. The data are unclear but suggest allograft tissue leads to longer remodeling times and incorporation in the bone tunnels as observed with autograft tissue.…”
Section: Discussionmentioning
confidence: 99%